ANALISIS PENYEBAB GIZI KURANG PADA BALITA - Dewi Safitri; Rusni Safitry; Wa Nuliana; Renita Afriza (Ensiklopedia Research and Community Service Review, 2026)
Malnutrition in toddlers is one of the public health issues that remains a serious concern, especially in developing countries, including Indonesia. Based on data obtained from the Lubuk Buaya Community Health Center during the last three months, from July to August 2025, it is known that malnutrition in toddlers is still high. The purpose of this study is to analyze the causes of malnutrition in toddlers. The research design used in this study was cross-sectional. The research was conducted in the Lubuk Buaya Community Health Center working area. The research was conducted in November 2025. The research population consisted of mothers who had toddlers in the Lubuk Buaya Community Health Center working area. The sample consisted of 70 respondents. The sampling technique used was purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between mothers' knowledge (p value: 0.046) and dietary patterns (p value: 0.000) and malnutrition in toddlers. It is recommended that health centers, through health workers and posyandu cadres, make greater efforts to improve educational activities that can increase mothers' knowledge about the importance of providing good nutrition to their toddlers. Keywords: Toddlers, Mother's Knowledge, Diet.